Hemin_Induced Changes in the Red Blood Cell Membrane Structure - V. V. Moroz; E. K. Kozlova; A. M. Chernysh; O. E. Gudkova; A. V. Bushuyeva (Общая реаниматология, 2012)
Objective: to determine whether the supplementation with hemin affects the nanostructure of red blood cell memranes. Subjects and methods. Human whole blood was supplemented or not with hemin and nanostructure of red blood cell membranes was studied using atomic force microscopy. Conclusion. Experiments demonstrated that hemin exerted a specific effect on the nanostructure of red blood cell membranes to form domains upon their surface. The size of granular structures in the domains was 100—200 nm, which coincides with that of a spectrin matrix. The effect of domain generation possesed threshold character starting from hemine concentrations of 1.3—1.7 mM. These results demonstrate the potential of the use of nanostructural changes within the erythrocyte membrane as surrogate biomarkers of erythrocyte response to hemoglobin derivatives in future studies. Key words: red blood cell membranes, hemin, nanostructure, atomic force microscopy.